Mitigating Polarization in Ethiopia's Political System: An Adversarial Collaboration Framework - Goshu, Belay (Academia Journal of Humanities & Social Sciences, 2025)
Ethiopia's political landscape, shaped by ethnic-based federalism since 1991, has experienced escalating polarization and conflict, notably the Tigray War (2020–2022) and post-Hachalu Hundessa violence. This study examines the roles of government, the private sector, and social media in stabilizing peace and narrowing the political divides. Therefore, the major objective of this paper is to assess their contributions and propose a collaborative model for peacebuilding. A mixed-methods approach was employed, integrating quantitative data analysis from 150 stakeholders with qualitative insights from 20 interviews and three focus group discussions (FGDs). The findings revealed the government's leading impact (0.60) on peace stabilization, followed by the private sector (0.40) and social media (0.30), with polarization reducing from 0.74 to near 0.0 over five years (see Figures 5 and 6). Strong correlations (r = 0.74) between ideological distance and ethnic tension underscored ethnic federalism's role. The findings of the study conclude that a multi-stakeholder approach, leveraging structured dialogue and institutional reforms, can effectively mitigate polarization and foster stability. Recommendations include government-led reforms, private-sector investments in infrastructure, social media regulation to counter misinformation, and a coordinated platform for monitoring progress. These findings offer a replicable framework for Ethiopia and similar polarized contexts.